Market runs of hedge funds during financial crises - Sangwook Sung; Hoon Cho; Doojin Ryu (Kiel Institute for the World Economy (IfW), 2019)
A hedge fund's capital structure is fragile because uninformed fund investors are highly loss sensitive and easily withdraw capital in response to bad news. Hedge fund managers, sharing common investors and interacting with each other through market price, sensitively react to other funds' investment decisions. In this environment, panic-based market runs can arise not because of systematic risk but because of the fear of runs. The authors find that when the market regime changes from a normal state to a "bad" state (in which runs are possible), hedge funds reduce investment prior to runs. In addition, the market runs are more likely to occur in a market where hedge funds hold greater market exposure and uninformed traders have greater sensitivity to past price movement.
Keywords: G01; G23; 330; market sustainability; market runs; hedge funds; limits of arbitrage; financial crises; synchronization risk